An Effective performance Management System: Empirical study from Saudi Arabia - Saeed M Al saif (SEISENSE Journal of Management, 2018)
The goal of the paper is to find the characteristics which can lead to an effective performance management systems. The paper suggested a model with a set of characteristics in three critical intervals for the performance management process: when identifying performance objectives, when measuring performance, and when developing performance.